Spontaneous 180-Degree Rotatory Dislocation of Rotating-Platform Total Knee Arthroplasty - Stephen Sierra; Chibuzo Akalonu; Kevin West; Matthew Blue; George Brindley (Case Reports in Orthopedics)
Rotating-bearing total knee arthroplasty has been theorized to have some advantages in the kinematics and wear characteristics of total knee arthroplasty. A rare complication of rotating-bearing total knee arthroplasty is rotary dislocation, spinout, of the polyethylene component. When these dislocations occur, they typically result in a 90-degree dislocation in respect to the axial axis of the knee. This case is unique in that it presents a complete 180-degree polyethylene dislocation without trauma.